Role of enhanced half‐life factor VIII and IX in the treatment of haemophilia. (7th March 2015) - Mahdi, Ali J.; Obaji, Samya G.; Collins, Peter W.
Summary Treatment of congenital haemophilia with factor VIII and IX concentrates often requires frequent infusions. This has obvious implications in establishing effective administration strategies and, in turn, adherence. To overcome these issues, three main technologies – polyethylene‐glycol, Fc‐neonatal IgG1 and albumin fusion products – have emerged into various stages of clinical development. Published data indicates an approximately 1·5‐ and fivefold increase in half‐life of factor VIII and IX, respectively, compared to standard recombinant concentrates. Studies into efficacy and safety are starting to be published. Monitoring and optimal use of these new concentrates remains unknown. Weekly factor IX prophylaxis appears to be a feasible prophylactic regimen in haemophilia B patients. Weekly longer‐acting FVIII is unlikely to provide adequate prophylaxis in most patients with haemophilia A but may reduce the frequency of infusions. Ongoing clinical trials and real life experience will help shape how these products can be used in practice and their cost effectiveness. The drive for convenience however should not overshadow the ultimate goal of prophylaxis, namely, preventing bleeding and arthropathy.